Distinctive picosecond spin polarization dynamics in bulk half metals - Battiato, Marco (2018)
Femtosecond laser excitations in half-metal (HM) compounds are theoretically predicted to induce an exotic picosecond spin dynamics. In particular, conversely to what is observed in conventional metals and semiconductors, the thermalization process in HMs leads to a long living partially thermalized configuration characterized by three Fermi-Dirac distributions for the minority, majority conduction, and majority valence electrons, respectively. Remarkably, these distributions have the same temperature but different chemical potentials. This unusual thermodynamic state is causing a persistent nonequilibrium spin polarization only well above the Fermi energy. Femtosecond spin dynamics experiments performed on Fe3O4 by time- and spin-resolved photoelectron spectroscopy support our model. Furthermore, the spin polarization response proves to be very robust and it can be adopted to selectively test the bulk HM character in a wide range of compounds.